SMA Plus Al-Azhar Jember Students' Scientific Literacy on Biodiversity Course - Romlah, Siti; Sahadha, Moch Hanif Nur; Hakiki, Winda Nur; Anggariny, Laylatul Vayzah (META: Journal of Science and Technological Education, 2023)
The objective of this study is to determine the Scientific Literacy Profile of SMA Plus Al-Azhar Students in Class X Biology Learning on Biodiversity Material. This study was conducted during the even semester of the academic year 2022-2023. This study provides treatment in learning activities using a pre-experimental design and a one-group pre-test post-test design. Using a Google form containing 10 questions, data was gathered employing a 10-item questionnaire. In this research, 28 class X SMA Plus Al-Azhar Jember students formed the population. In the present study, qualitative descriptive data analysis techniques were used to analyze the data. 61% of the research findings on content indicators fall into the adequate category. The category for cognitive process indicators is poor, with a percentage of 40%, and the category for context indicators is very poor, with a percentage of 39%.